Analysis Of The Role Of The Midwife In Hospital In Stunting Prevention Effort In Rsu Aulia, Jakarta Selatan - Dita Aprillia; Jenny Anna Siauta; Rukmaini (Science Midwifery, 2022)
Stuntingis a problem of particular concern in Indonesia and the world. Midwives as implementers and managers of health services must be able to utilize their resources effectively and efficiently in improving the health status of mothers and children so that they can contribute to stunting prevention efforts. This study aims to analyze the role of midwives in stunting prevention efforts at Aulia General Hospital, South Jakarta. This study uses an analytical survey design with a cross sectional approach. The sample, namely midwives who work at the Aulia General Hospital, South Jakarta, amounted to 112 people. The sampling technique used was purposive sampling. The instrument uses a google form questionnaire. Bivariate analysis using chi square test. The results of the study from 112 midwives who worked at RSU Aulia, South Jakarta, obtained 72.3% of midwives performed their role well in stunting prevention efforts. Bivariate analysis obtained all variables of education (p value 0.032), motivation (p value 0.000), knowledge (p value 0.001), training (p value 0.019), health facilities (p value 0.023), and SOP guidance (p value 0.025) < 0.05 was significantly related to the role of midwives in stunting prevention efforts. It is recommended that midwives improve their professional work through education to a higher level and increase competence through training or seminars on 1000 HPK. training (p value 0.019), health facilities (p value 0.023), and SOP guidelines (p value 0.025) <0.05 were significantly related to the role of midwives in stunting prevention efforts. It is recommended that midwives improve their professional work through education to a higher level and increase competence through training or seminars on 1000 HPK. training (p value 0.019), health facilities (p value 0.023), and SOP guidelines (p value 0.025) <0.05 were significantly related to the role of midwives in stunting prevention efforts. It is recommended that midwives improve their professional work through education to a higher level and increase competence through training or seminars on 1000 HPK.